Laser biospeckle as a method to investigate the short-term effects of far-red light on an arugula (Eruca sativa Mill) plant - Igarashi, Hibiki; Baba, Takeshi; Takemura, Kairi; Kono, Takahiro; Kadono, Hirofumi; Yamada, Jun; Rajagopalan, Uma Maheswari (Frontiers in Plant Science, 2025)
With rapid climate change, it has been increasingly difficult to grow different crops, and as an alternative method, artificial cultivation in controlled environments has evolved into a new sustainable agriculture practice. However, the cost of having a controlled environment has become a major issue, and investigations have been conducted to develop cost-saving and efficient cultivation techniques. One research focus is on the utilization of stimulating appropriate photoreceptors for a certain time by far-red (FR) light to influence plant development. Here, we propose a novel laser biospeckle method, a non-destructive and real-time measurement method for the speedy evaluation of FR effects on arugula (Eruca sativa Mill) plants. Laser biospeckles are formed from the interference of scattered light from the organelles within the biological tissue, and the intensity of such speckles varies due to displacements within the tissue. In the experiment, while illuminating with FR and red (R) LED light of 735 nm and 630 nm, respectively, for a duration of 120 s to 300 s, the leaves of an arugula plant were irradiated simultaneously with laser light of 852 nm to obtain biospeckles. Video clips were recorded using a complementary metal-oxide-semiconductor (CMOS) camera at 15fps for 20 s. Correlations between the first and the subsequent frames were calculated to investigate the differences in the internal activity with exposure to FR and were characterized by a parameter named biospeckle activity (BA). Experiments were done with the healthiness and the age of the plant as parameters. It was found that depending on the healthiness of the plants, under short durations of 120s FR, BA and thus the internal activity within the leaves increased compared to the long duration of 300s FR. Further, a 1-month-old plant was found to have a faster decay of correlation and thus a steep increase in BA compared to that for a 3-month-old plant. Our results suggest that BA could be used as a measure to investigate the effects of FR or FR plus R in plant development within a timeframe of a few minutes, and thus can be employed as a complementary measurement technique for the speedier investigation of FR effects on plants.